Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.31538/munaddhomah.v3i1.231
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum Development Management at Madrasah Aliyah Negeri

Abstract: This study aims to determine how the management of curriculum development in MAN Padang Lawas Utara. This research used a qualitative approach with a descriptive type. Data collection techniques used observation, interviews and documentation techniques to obtain valid data about curriculum development management at MAN Padang Lawas Utara. Based on the results of the study, it shows that 1) The planning of curriculum development at MAN Padang Lawas Utara is quite good, which includes: the background of the prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…In African contexts, teacher professional development is considered crucial for improving classroom practices and enhancing the quality of education (Ajani, 2022;Govender & Ajani, 2021). Studies have emphasized the need for relevant teaching resources, regular professional development activities, and the involvement of teachers in program design (Ajani, 2022;Pohan et al, 2022). The literature highlights the importance of addressing teachers' classroom needs and supporting their professional growth (Ogegbo et al, 2019;Ajani, 2022;Govender & Ajani, 2021).…”
Section: The Concept Of Teacher Professional Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…In African contexts, teacher professional development is considered crucial for improving classroom practices and enhancing the quality of education (Ajani, 2022;Govender & Ajani, 2021). Studies have emphasized the need for relevant teaching resources, regular professional development activities, and the involvement of teachers in program design (Ajani, 2022;Pohan et al, 2022). The literature highlights the importance of addressing teachers' classroom needs and supporting their professional growth (Ogegbo et al, 2019;Ajani, 2022;Govender & Ajani, 2021).…”
Section: The Concept Of Teacher Professional Developmentmentioning
confidence: 99%
“…The effectiveness of professional development programs in African contexts has been a topic of interest (Mayombe, 2023). Some studies have identified challenges in implementing these programs, such as limited implementation of new practices by teachers (Andersson & Palm, 2018;Pohan et al, 2022). There is a need for comprehensive and dynamic professional development models that consider teachers' learning needs and school environments (Ogegbo et al, 2019;Govender & Ajani, 2021).…”
Section: The Effectiveness Of Professional Development Programsmentioning
confidence: 99%
See 2 more Smart Citations
“…IRE within MAN schools aims not only to convey religious knowledge but also to instill Islamic values, beliefs, and practices in students. This combination of faith-based education with academic learning fosters a comprehensive understanding of Islam, equipping students with the tools to navigate both their spiritual and worldly lives [26], [31].…”
Section: Islamic Religious Education In Man Schoolsmentioning
confidence: 99%